A comment on Singular and nonsingular black holes using the Gaussian distribution - Batic, D.; Nowakowski, M. [UNESP]; Salim, S. A. (World Scientific Publishing, 2023)
In this work, we join the controversial discussion on singular and nonsingular black holes using the Gaussian distribution. Our result which uses correct boundary conditions shifts the debate in favor of regular black holes at the center. The present findings add new insights into the ongoing discussions surrounding singularities in black hole solutions of the Einstein equations.
Keywords: general relativity; noncommutative geometry inspired black holes; Regular black holes